Karakterisasi Jamur Mikroskopis di Kawasan Kampus Universitas PGRI Banyuwangi - Irqami Rachma; Tristi Indah Dwi Kurnia (Jurnal Pendidikan Biologi Undiksha, 2025)
Fungi have a very important role in an ecosystem, in terms of ecology fungi are used as decomposers and biodiversity balancers. This study aims to determine the genus of microscopic fungi in the campus area of PGRI Banyuwangi University. The research used a qualitative with a type of descriptive research type. The subject of this research is all microscopic fungi and the object of research is the genus of microscopic fungi in the campus area of PGRI Banyuwangi University, Kertosari Village. The research stages consist of preparation, implementation and data analysis. The observation of microscopic fungi was carried out macroscopically and microscopically. The results showed that there were three genus of fungi, namely the genus Trichoderma, Rhizopus, and Aspergillus. Each isolate has distinctive morphological characteristics, both in terms of colony color, growth form, and microscopic structure.